The evolution and forms of decentralisation in Zimbabwe : experiences from post-independence era, 1980 to 2019 - Musekiwa, N. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
This paper provides an overview of the political and administrative journey taken towards implementing decentralisation in local government context in Zimbabwe since independence in 1980 to 2019. This paper identifies the key landmarks along the way, in terms of legislation, policies, programmes, institutions and actors. The paper reflects on specific Zimbabwean experiences with this complex process, of progress made, and of the lessons that emerge, the challenges, successes, and failures. The guiding question is how decentralisation has evolved and been adopted in Zimbabwe in the post-colonial era? Decentralisation in Zimbabwe as influenced by the global trends evolved from being state centric to individual centric and encompassing stakeholders from the state to individual levels. Legislation on decentralisation in Zimbabwe has been advanced though the practice has been deficient
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Decentralisation; Local government; Rural District Councils; Urban Councils; Local government--Zimbabwe; Public administration